2006
DOI: 10.1051/0004-6361:20064904
|View full text |Cite
|
Sign up to set email alerts
|

The XMM-Newton survey of the ELAIS-S1 field

Abstract: Aims. The formation and evolution of cosmic structures can be probed by studying the evolution of the luminosity function of the Active Galactic Nuclei (AGNs), galaxies and clusters of galaxies and of the clustering of the X-ray active Universe, compared to the IR-UV active Universe. Methods. To this purpose, we have surveyed with XMM-Newton the central ∼0.6 deg 2 region of the ELAIS-S1 field down to flux limits of ∼5.5 × 10 −16 erg cm −2 s −1 (0.5-2 keV, soft band, S), ∼2 × 10 −15 erg cm −2 s −1 (2-10 keV, ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
96
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(111 citation statements)
references
References 53 publications
15
96
0
Order By: Relevance
“…Basilakos et al (2004) found results consistent with ours (γ − 1 = 1.2 ± 0.3 and θ 0 = 48.9 +15.8 −24.5 arcsec) but with much larger error bars. Puccetti et al (2006) are also in agreement with us (θ 0 = 12.8 ± 7.8 arcsec) within their large uncertainties. For a canonical slope of 0.8, Yang et al (2003) found θ 0 = 40±11 arcsec, much larger than ours (θ 0 = 5.9±0.3 arcsec) with a significance of ∼4σ.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Basilakos et al (2004) found results consistent with ours (γ − 1 = 1.2 ± 0.3 and θ 0 = 48.9 +15.8 −24.5 arcsec) but with much larger error bars. Puccetti et al (2006) are also in agreement with us (θ 0 = 12.8 ± 7.8 arcsec) within their large uncertainties. For a canonical slope of 0.8, Yang et al (2003) found θ 0 = 40±11 arcsec, much larger than ours (θ 0 = 5.9±0.3 arcsec) with a significance of ∼4σ.…”
Section: Resultssupporting
confidence: 91%
“…Summary of the fits in different flux-limited subsamples. (Yang et al 2003), COSMOS (Miyaji et al 2007), XMM-2dF (Basilakos et al 2004(Basilakos et al , 2005, ELAIS-S1 (Puccetti et al 2006), XMM-LSS (Gandhi et al 2006) and AXIS ). In Fig.…”
Section: Dependence On the Flux Limitmentioning
confidence: 99%
“…In the other energy bands our fits reproduce well the behaviour of the log N − log S relations also at the bright end side, though the bright end slopes remain slightly flatter that the canonical α 1 = 2.5. The data are compared to those obtained in the XMM-COSMOS survey , the HELLAS2XMM survey (Baldi et al 2002), the compilations of X-ray surveys produced by Moretti et al (2003) and Hasinger et al (2005), the Beppo-Sax survey (Fiore et al 2001;Giommi et al 2000), the Chandra deep surveys CDFN and CDFS (Rosati et al 2002;Bauer et al 2004), the RDSS (Hasinger et al 1993), the extended CDFS (Lehmer et al 2005), the ELAIS-S1 survey (Puccetti et al 2006) and the XMM-HBS survey (Della Ceca et al 2004). The black dashed lines represents the prediction of the X-ray background model of Gilli et al (2007).…”
Section: Number Countsmentioning
confidence: 99%
“…While XMM-Newton surveys cannot probe very faint fluxes as Chandra, they provide good quality spectroscopy in the whole 0.5−8 keV band for a large number of sources. The large effective area of XMM-Newton has been exploited in several surveys, including the Lockman Hole (with 1 Ms of exposure, Brunner et al 2008), the ELAIS-S1 field (Puccetti et al 2006), COSMOS , and 2XMM (Mateos et al 2008).…”
Section: Introductionmentioning
confidence: 99%